Taxation and the philosophy of Frédéric Bastiat - McGee, Robert (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
Frederic Bastiat (1801-1850) was an economist and journalist. A member of the French Liberal School, he is best known for his free trade ideas and his philosophy of law. Mark Blaug ranks him as one of the 100 greatest economists before Keynes. Schumpeter called him a brilliant economic journalist. Haney devoted a chapter of his History of Economic Thought to Bastiat.Although Bastiat is known for his work on free trade and the philosophy of law, he also wrote on other topics. To date, almost no one has examined his views on taxation. The purpose of this paper is to fill that gap in the literature.
Keywords: taxation; utilitarian; rights theory; public finance; French liberalism; Frédéric Bastiat